การวิเคราะห์และเทียบเคียงผลการดำเนินงานด้านการผลิต ของโรงงานหล่อเหล็ก - เศรษฐศาสตร์ รักใหม่ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this thesis is to analyze and benchmark manufacturing performance of cast iron factory by using benchmarking technique as a tool for researching. The phases of benchmarking process in this research composed of 4 steps. The first step is to select the process, the benchmarking study will focus on, by considering the process impact on company’s manufacturing performance indicator (PI) which is highly important while the performance is low. The second step is to search for and identify suitable benchmarking partner. The third step is to collect data in partner factory. And the last step is to analyze and summarize the difference in methods performed between case study factory and the partner. Types of critical success factor (CSF) identified in this thesis emphasized on quality (Q), cost (C), delivery (D), safety (S) and morale (M). %Claim, %defect and OEE are PI in ด type. Material yield, cost structure and inventory turnover are c type. %On-time delivery is D type. Employee turnover and labor efficiency are M type. Accident frequency rate is S type. After comparing the manufacturing performance level of case study factory against other cast iron factories, it was concluded that %claim’s performance level of case study factory was the lowest, 3.43%, while %claim of selected benchmarking partner factory was 0.8%. So, %claim was the first PI improvement to be focused on.